Health and household environment factors linked with early alcohol use in adolescence: a record-linked, data-driven, longitudinal cohort study - Bandyopadhyay, Amrita; Brophy, Sinead; Akbari, Ashley; Demmler, Joanne; Kennedy, Jonathan; Paranjothy, Shantini; Lyons, Ronan; Moore, Simon (International Journal of Population Data Science, 2022)
Introduction Early alcohol use has significant association with poor health outcomes. Individual risk factors around early alcohol use have been identified, but a holistic, data-driven investigation into health and household environmental factors on early alcohol use is yet to be undertaken. Objectives This study aims to investigate the relationship between preceding health events, household exposures and early alcohol use during adolescence using a two-stage data-driven approach. Methods In stage one, a study population (N=1,072) were derived from the Millennium Cohort Study (MCS) Wales (born between 2000-2002). MCS data were first linked with electronic-health records. Factors associated with early (<= eleven years old) alcohol use were identified using feature selection and stepwise logistic regression. In stage two, analogous risk factors from MCS were recreated for whole population (N=59,231) of children (born between 1998-2002 in the Welsh Demographic Service Dataset) using routine data to predict the alcohol-related health events in hospital or GP records. Results Significant risk factors from stage two included poor maternal mental (adjusted odds ratio [aOR]=1.31) and physical health (aOR=1.25), living with someone with alcohol-related problem (aOR=2.16), single-adult household (aOR=1.45), ever in deprivation (aOR=1.66), child's high hyperactivity (aOR=3.57), and conduct disorder (aOR= 3.26). Children with health events, whose health needs are supported (e.g., are taken to the doctor), are at lower risk of early alcohol use. Conclusion Health events of the family members and the child can act as modifiable exposures and may therefore inform the development of prevention initiatives. Families with known alcohol problems, living in deprivation, experiencing child behavioural problems and those who are not taken to the doctor are at higher risk of early drinking behaviour and should be prioritised for early years support and interventions to target problem drinking in young people.